The Effect of Intensity of Watching “Anak Jalanan” TV Series and Parental Mediation towards Violent Behavior Done by Children - Puji Susanti; Dra. Sri Widowati Herieningsih, MS (Interaksi Online, 2016)
Today, there are so many violent cases which are done by children. Meanwhile, Television, as the most consumed medium, mostly shows violent programs which one of the example is Anak Jalanan TV series. Children in their development stages are feared to imitate the violence because of what they have watched in television. Nevertheless, there is a possibility of another factor such as parental mediation in children’s television consumption. The purpose of this study is to understand the influence of the intensity of watching “Anak Jalanan” TV series and parental mediation towards violent behavior by children. The theories that are used in this study are the Social Learning Theory and Parental Mediation Theory. This study is an explanatory research with 100 samples which are taken by using non-probability sampling techniques. The hypothesis testing in this study uses Linear Regression analysis which is performed after passing the classical assumption test and Pearson Product Moment correlation test. The result of the classical assumption test in this study is qualified to become a regression model, but the significant value of the three dependent variables, according to the result of correlation test, are bigger than 0,05. The significant value of those three dependent variables are 0,255 of the intensity of watching “Anak Jalanan” TV series; 0,614 of restrictive mediation variable and 0,165 of active mediation variable. The result of correlation test shows that the three independent variables do not have relation with the violent behavior by children. The absence of the relation indicates that there is no influence of the intensity of watching “Anak Jalanan” towards violent behavior by children, the influence of restrictive mediation towards violent behavior by children and the influence of active mediation towards violent behavior by children. All the hypotheses in this study are rejected. It means that all the violent behavior by children are more influenced by other factors beyond the intensity of watching “Anak Jalanan” TV series and parental mediation.